Pengaruh Kepemimpinan Kepala Sekolah, Supervisi Pengawas Terhadap Disiplin Kerja Guru Melalui Motivasi Kerja - Mas’ud; Indra Prasetyo; Woro Utari (CV. ALIM'SPUBLISHING, 2023)
The purpose of this study was to describe and analyze the influence between the principal's leadership and supervisory supervision on teacher work discipline through teacher work motivation as an intervening variable in the Office of the Regional Coordinator for Education, Rangsang District, Meranti Islands Regency. This type of research is explanatory research and the research approach is quantitative. The population in this study were all teachers in the Regional Coordinator of the Field of Education, Rangsang District, Meranti Islands Regency, totaling 54 people, the sample was determined to be 54 people using the census sampling method. Data was collected by documentation, literature study and questionnaires and then analyzed using Partial Least Square (PLS). The results showed that respondents rated the variables of teacher work discipline, work motivation, leadership and supervision in the criteria High, Leadership has a significant effect on work motivation, Supervision has a significant effect on work motivation, Leadership has no significant effect on work discipline, Supervision has a significant effect on work discipline, Work motivation has a significant effect on work discipline, Leadership has no significant effect on work discipline through motivation, Supervision has a significant effect on work discipline through motivation.